Strategic Role of Environmental Factors in the Operation of a Manufacturing Company: A Synthesis of Three Analytical Models - Stefán, Barbara Zsófia (International Journal of Engineering and Management Sciences, 2025)
Nowadays, the operations of companies are influenced by increasingly complex internal and external factors, the systematic examination of which is essential for conscious strategy-making. The relevance of this study lies in the context of global economic instability, rapid technological advancement, and intensifying market competition, all of which present new challenges for organizations. The aim of the research is to demonstrate how the analysis of environmental factors can support strategic decision-making, with particular emphasis on a specific company case. The analysis was based on three established methods—PESTEL analysis, Porter’s Five Forces model, and the SWOT framework—which together enabled an integrated examination of macro- and micro-environmental factors as well as internal resources. The results highlighted several key strengths of the company, such as professional expertise, international presence, and the quality of customer relationships, while also identifying several areas in need of improvement, particularly in terms of pricing strategy, digital information accessibility, and internal communication. The novelty of the study lies in the combined application of the three analytical tools, which revealed interrelated insights and served as the basis for well-founded recommendations aimed at enhancing strategic flexibility and strengthening competitiveness.